The Effect of 7P Marketing Mix on Purchasing Decisions For Gudeg Kaleng Bu Tjitro 1925 Original Variant at CV. Buana Citra Sentosa Yogyakarta - Kumalasari, Dian Dewi; Nurmastiti, Ardela; Puspitaningrum, Dwi Aulia (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
This research was conducted in response to the growing business landscape, which requires companies to carefully strategize their marketing approaches to enhance sales performance. CV. Buana Citra Sentosa, a company offering four variants of canned gudeg, positions its Gudeg Kaleng Bu Tjitro 1925 original variant as the flagship product. The objective of this study is to assess how the marketing mix at CV. Buana Citra Sentosa affects purchasing decisions and customer satisfaction. Ensuring the timely supply of raw materials and inventory management is critical for maintaining an efficient and rapid production process, thus meeting both consumer demand and the company's operational goals. The research surveyed 80 customers who had purchased the Gudeg Kaleng Bu Tjitro 1925 original variant. Utilizing multiple linear regression analysis via SPSS 24 for Windows, the findings revealed that all marketing mix variables—product, price, place, promotion, people, physical evidence, and process—collectively have a significant impact on purchasing decisions. Additionally, each variable independently influences purchase decisions for the Gudeg Kaleng Bu Tjitro 1925 product at CV. Buana Citra Sentosa in Yogyakarta.